Implementation of The Nahwu Abstract Method in Improving The Ability to Read The Book of Fath Al-Qarib - Abidin, Muhammad; Umam, Khoirul (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2019)
This article analyzes the implementation of the Nahwu Abstract book as a method in increasing the ability to read the FathÂ al-QarÄ«b book in the private vocational school of Ibtidaâ€™iyah Islamiyah Genukwatu Ngoro Jombang. Nahwu Abstract is according to Nahwu science taken from various preferred Nahwu books such as JurÅ«mÄ«yah, ImrÄ«thi, AlfÄ«yah and other Nahwu books. This Nahwu book is called Nahwu science which is taken from various preferred Nahwu books such as Jurumiah, Imrithi, Alfiyah and other Nahwu books, and this Nahwu book is called the rules of Nahwu. I concluded as follows: (1) Implementation of the Nahwu Abstract method for beginners to improve the ability to read the book FathÂ al-QarÄ«b. Conducted during study hours and at additional hours. In teaching teachers, use other methods such as sorogan. (2) Supporting factors for the implementation of the Nahwu Abstract method: professional teachers, approved books, students who are interested in learning the Nahwu Abstract method, the pesantren environment and additional jams twice in the update. (3) Obstacles and solutions to the application of the Nahwu Abstract method: lack of class hours, the solution is to hold extra hours, not all students take extra hours, the solution involves extra hours, noise during study hours, the solution is to move to the mosque and to the parentsâ€™ home.